Обґрунтування авторської методики дослідження емоційного інтелекту - Бутенко, М. В.; Butenko , M. V. (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 3 (102), ч. 2. - С. 257-270, 2023)
Проаналізовано поняття емоційного інтелекту, емоційної компетентності та структурні складові цих понять. Виокремлено головні компоненти емоційного інтелекту та розроблено власний тестовий інструментарій щодо його вивчення. Здійснено кореляційний аналіз показників авторської методики з наявними тестовими методами вивчення емоційного інтелекту з метою підтвердження надійності та валідності тесту. Доведено валідність і надійність розробленого тесту, який рекомендується використовувати для оцінки рівня емоційного інтелекту та його компонентів.

Emotional intelligence is one of the new concepts in psychology, which is constantly being studied by many scientists. The article analyses the concepts of emotional intelligence, emotional competence and its structural components. The article considers various concepts of emotional intelligence of such scientists as P. Salovey, D. Mayer, D. Caruso, G. Gardner, R. Bar-On, S. Marcus, G. Dudchak, M. Mykolaychak. The article also analyses domestic concepts of emotional intelligence. As a result of the analysis of various scientific views on the concept of emotional intelligence and methods of its research, it has been made a decision to develop the author’s own psychodiagnostic test. The author has developed own test methodology for studying the emotional component, since there are no similar test methods in the national psychodiagnostics. The author's methodology includes five main and two additional scales. The main scales of the methodology include the following properties of emotional intelligence: 1. managing one’s own emotions; 2. managing the emotions of others; 3. understanding one’s own emotions; 4. understanding the emotions of others; 5. empathy. Additional scales of the methodology are the lying scale and the general level of emotional intelligence (calculated by adding the results of the 5 main scales). Subsequently, various test methods were considered to study emotional intelligence and its components. The following tests were chosen for correlation: Toronto Alexithymia Scale, N. Hall’s Self-Esteem Emotional Intelligence Inventory, and the Profile of Emotional Competence (PEC). A correlation analysis of the own methodology with existing test methods for the study of emotional intelligence has been carried out to confirm its validity. The study proved the validity and reliability of the developed test methodology. Therefore, the developed test methodology is indeed aimed at studying the general level of emotional intelligence and studying its components such as: managing one's own emotions and the emotions of others, understanding one's own emotions and the emotions of others, empathy.

Проанализированы понятия эмоционального интеллекта, эмоциональной компетентности и структурные составляющие этих понятий. Выделены главные компоненты эмоционального интеллекта и разработан собственный тестовый инструментарий для его изучения. Проведен корреляционный анализ показателей авторской методики с имеющимися тестовыми методами изучения эмоционального интеллекта с целью подтверждения надежности и валидности теста. Доказана валидность и надежность разработанного теста, который рекомендуется использовать для оценки уровня эмоционального интеллекта и его компонентов.
Justification of the author’s methodology of emotional intelligence research
Keywords: емоційний інтелект; структура емоційного інтелекту; погляди вчених; методика тестування; тестовий матеріал; emotional intelligence; structure of emotional intelligence; views of scientists; theoretical approaches; emotional competence; test material; correlation; эмоциональный интеллект; структура эмоционального интеллекта; взгляды ученых; методика тестирования; тестовый материал